Análisis de los costos de producción de mora rubus y los ingresos en los pequeños agricultores del sector Jalubí, del cantón Pallatanga, provincia de Chimborazo - Orellana de la Rosa, Thelmo Abraham (2017)
With the rise of emerging economies, the demand for jobs is constantly growing and despite this there is a decrease in job offers. The research was carried out in Jalubí Sector, Canton Pallatanga, province of Chimborazo, Jalubí Sector is mainly engaged in the production of Mora and Frejol, but in spite of its large production it maintains several problems as far as production, all this due to the lack of knowledge regarding the costs of production that for lack of knowledge tend to be very high compared to their income. The purpose of our project is to provide the best solutions to this problem to small farmers in the Jalubí Sector in order to improve their profits and their level of life. For this reason an exploratory study was carried out since there is no written antecedent of said problem in the production costs of the Mora in this Sector. Surveys targeted pecifically at small farmers were carried out so as to obtain fundamental information on the management of production costs so as to be able to know what their shortcomings are, to provide the best solution and to contribute to society…..